TWO CASES OF ANAPLASTIC LARGE CELL LYMPHOMA DEMONSTRATING INVOLVEMENT AT A RANGE OF EXTRA-NODAL TISSUES. (February 2015) - Cummins, Katherine D.; Pham, Alan; Kelsey, Giles
Abstract : Aim: To describe two cases of anaplastic large cell lymphoma, and to demonstrate the disease histologically at numerous extra-nodal sites. Methods: Patient A is a 67-year-old male with malena and B-symptoms, and extensive lymphadenopathy. Patient B is a 55-year-old HIV-infected male with malaise and B-symptoms, and acute renal failure due to obstructive nephropathy, secondary to extensive retroperitoneal lymphadenopathy. Results: Histopathological specimens from both patients will be shown, demonstrating disease involvement in peripheral blood, bone marrow aspirate and trephine, lymph nodes, urine cytology and also invading skeletal muscle. PET imaging for one patient is included, remarkable for the extent of disease involvement. The poster presentation will demonstrate photos of these specimens, and will incorporate a suggested algorithm for the histopathological diagnosis of anaplastic large cell lymphoma. Conclusion: These two cases demonstrate two different presentations of anaplastic large cell lymphoma, with different ALK-mutation status, variable degrees of extranodal disease involvement demonstrated on peripheral blood, bone marrow aspirate and trephine, urine cytology and infiltrating skeletal muscle, in addition to PET imaging.